Triplophyllum juruenense (Tectariaceae), a new species of fern from Southern Amazonia - Nunes, Mauricio G.; Prado, Jefferson; Hirai, Regina Y.; Labiak, Paulo H. (Phytotaxa, 2025)
Triplophyllum is a pantropical fern genus found in the tropical forests of Madagascar, Western Africa, and the Neotropics. In the Neotropics, most of its species have a wide distribution in the lowlands of the Amazon, with some reaching the foothills of the Andes and the Guyana Shield at the Amazonian borders, Central America and the Antilles, as well as the Atlantic Forest in northeastern and southeastern Brazil. Recent collections in the southern limits of the Amazon have revealed an undescribed species, which is described herein as Triplophyllum juruenense. This species is restricted to the meridional portion of the Amazon, where the tropical Amazonian forest meets the drier vegetation of Central Brazil. The new species is described and compared to its closest relatives. Illustrations and a distribution map are also provided.